KARALNOŚĆ USIŁOWANIA NIEUDOLNEGO - Dębski, Ryszard (Wydział Prawa i Administracji UAM, 1999)
The Author - starting his considerations from a discussion of primary legislation that took into account only an alteration in outer world (no alteration = no punishment) - gives a survey of the revolution of dispositions of law within the scope of attempt to commit an act which is illegal (i.e. anti-social act) - and this - beginning from Roman law. Particular theories are then discussed (objective and subjective attempt theories, material theory, abstractive-objective theory, formal-objective theory, material-objective, general-objective and, finally, individual-objective theories). Among recent theories the concrete-objective one and the theory of a gap in essential factors that statutorily constitute an offence are mentioned. Differences between absolutely inapt attempt and relatively inapt one - what is a result of inappropriateness of the instrument of crime used in its real, qualitative, local or quantitative aspect - are also presented. When characterizing particular terms of this question the Author analyses the notion of inapt attempt against the background of rich literature of the subject and terminates his considerations with an evaluation of correspondent provisions within the newest Polish penal code that got into force in 199?. 98
PUNISHABILITY OF INAPT ATTEMPT